How Long-Term Contracts can Mitigate Inefficient Renegotiation Arising Due to Loss Aversion - Daniel Göller (ZBW - Leibniz Information Centre for Economics, 2021)
A loss-averse buyer and seller face an uncertain environment. Should they write a long-term contract or wait until the state of the world is realized? I show that simple long-term contracts perform better than insinuated in Herweg and Schmidt (2015), even though loss aversion makes renegotiation sometimes inefficient. During renegotiation, the outcome induced by the long-term contract constitutes the reference point to which the parties compare gains and losses induced by the renegotiated transaction. Whereas Herweg and Schmidt consider that the long-term contract is always performed, it should not in "bad" states. This alters the threat point in renegotiation, making it easier to renegotiate and thus improves the performance of long-term contracts. Specific performance contracts perform better than in Herweg and Schmidt but are still problematic. Option contracts perform much better since only one party has the ex-post trade decision making it much easier to prevent the contract is inefficiently enforced due to loss aversion. My findings suggest that loss aversion alone cannot explain why parties sometimes abstain from writing beneficial long-term contracts but give important insights on how long-term contracts should be written when parties are aware they are loss averse.
Keywords: D86; 330; Incomplete Contracts; Behavioral Contract Theory; Reference points; Holdup; Renegotiation